2001
DOI: 10.1002/jnr.10084
|View full text |Cite
|
Sign up to set email alerts
|

α‐cyano‐4‐hydroxycinnamate decreases both glucose and lactate metabolism in neurons and astrocytes: Implications for lactate as an energy substrate for neurons

Abstract: The rates of uptake and oxidation of [U-(14)C]lactate and [U-(14)C]glucose were determined in primary cultures of astrocytes and neurons from rat brain, in the presence and absence of the monocarboxylic acid transport inhibitor alpha-cyano-4-hydroxycinnamate (4-CIN). The rates of uptake for 1 mM lactate and glucose were 7.45 +/- 1.35 and 8.80 +/- 1.0 nmol/30 sec/mg protein in astrocytes and 2.36 +/- 0.19 and 1.93 +/- 0.16 nmol/30 sec/mg protein in neuron cultures, respectively. Lactate transport into both astr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
56
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 62 publications
6
56
0
Order By: Relevance
“…Thus, on this basis, it can be argued that lactate might represent a better oxidative substrate than glucose for neurons, at least in vitro. This conclusion is consistent with numerous other studies performed by measuring CO 2 production on synaptic terminals (McKenna et al, 1993(McKenna et al, , 1994(McKenna et al, , 1998, excised sympathetic ganglia (Larrabee, 1996), brain slices (Fernandez and Medina, 1986;Ide et al, 1969), and cultured neurons (McKenna et al, 2001;Tabernero et al, 1996;Vicario et al, 1991), all of which have shown preferential oxidation of lactate over glucose.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, on this basis, it can be argued that lactate might represent a better oxidative substrate than glucose for neurons, at least in vitro. This conclusion is consistent with numerous other studies performed by measuring CO 2 production on synaptic terminals (McKenna et al, 1993(McKenna et al, , 1994(McKenna et al, , 1998, excised sympathetic ganglia (Larrabee, 1996), brain slices (Fernandez and Medina, 1986;Ide et al, 1969), and cultured neurons (McKenna et al, 2001;Tabernero et al, 1996;Vicario et al, 1991), all of which have shown preferential oxidation of lactate over glucose.…”
Section: Discussionsupporting
confidence: 92%
“…Lactate can be used as an oxidative substrate in brain slices (Ide et al, 1969;Fernandez and Medina, 1986), cultured telencephalic neurons (Tabernero et al, 1996;McKenna et al, 2001), aggregated neuronal cultures (Honegger et al, 2002), sympathetic ganglia (Larrabee, 1996), and synaptic terminals (McKenna et al, 1993) and can be preferred to glucose (Bouzier-Sore et al, 2003;Itoh et al, 2003;Smith et al, 2003). In addition, metabolic demands increase neuronal ability to use lactate (Schurr et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, lactate has been proposed to function as an energy substrate for neurons recovering after glucose deprivation or a hypoxic insult (Fowler, 1993;Schurr et al, 1997a, b, c;Cater et al, 2001). However, much remains controversial and additional experiments seem pertinent to elucidate whether neurons in fact prefer lactate over glucose during synaptic activity (McKenna et al, 2001;Chih et al, 2001a). The present study represents an attempt to shed further light on this important question.…”
Section: Introductionmentioning
confidence: 95%